O desenvolvimento profissional e a construção da identidade do professor de educação física do ensino superior - Basei, Andréia Paula (2009)
This work is linked to the research line Formation, Knowledge and Professional Development of the Post-Graduation Program in Education of the Federal University of Santa Maria and aims to understand how occurs the construction of the identity of the teachers of higher education during its trajectory and professional development having reference on the teachers of the course of Physical Education, from the University of West of Santa Catarina, Campi of São Miguel do Oeste, and how it may influence in the educational activities developed for the formation of future teachers of Physical Education. The methodological options were for the qualitative approach and the study of case, the ethnographic type, that are linked to interest to unravel the path of teacher formation, the concepts and theories implicit in their pedagogical actions. So, we used as instruments of information s production: questionnaire, semistructured interviews, participant observation and documental analysis. The research was conducted at the University of West of Santa Catarina, Campi of São Miguel do Oeste, SC with three teachers of the course of Physical Education. For the analysis we used the technique of triangulation of the information obtained with the different instruments used, from which emerged categories of analysis according to the production of teachers meanings. Through the analysis developed from the viewpoint of the theoretical framework constructed for this research, we found that in the trajectory of formation of the teachers the initial training is more important when they reflect on their formation as teachers, detaching negative representations and wishing overcome. The formation course may influence in different ways the pedagogical actions taken by teachers, depending on the perspective that each builds with respect to their performance and their professional development, which enables us to conclude that the teaching is the confluence of several areas and times of the teachers life world. Believing that the teaching in the higher education needs a formative project and a collective professional development project, we pointed out as possible way to be trailed the guidance through the communicative rationality. This would provide a constitutive trajectory marked by the exchange of experiences, the collective construction of knowledge, of the be teacher and of emancipated subject able to speak and act in the construction of its life world.